PEMANFAATAN UBI UNGU (IPOMEA BATATAS L) UNTUK BAHAN DASAR PEMBUATAN PERMEN GEL - Kurnianingsih kurnianingsih; Faradila Agista (Garina, 2020)
Indonesia is an agricultural country that has great potential for the development of tropical fruits, horticultural crops and vegetables. Vegetables are important foods that are needed by the body because they contain nutrients needed by the body. However, some sweet potatoes that contain nutrients have not been adequately studied and utilized, including sweet potato (Ipomoea batatas L) from the Convulvulaceae family (Suparman, 2007). Sweet potato plants (Ipomoea batatas L) from 1968 until now have been widely produced, even Indonesia was the fourth largest country that produced sweet potato plants.The objectives of this study were: 1) Knowing the process of making purple sweet potato Gel candy; 2) Knowing consumer acceptance of purple sweet potato Gel candy products; 3) Knowing the nutritional content of purple sweet potato Gel candy. The methods used in this research include literary, documentation, experimental, organoleptic, hedonic and nutritional content methods. The resulting data is then processed and evaluated and then presented in tables and diagrams with in-depth explanations.The results showed that the best formula composition is found in code 472 The characteristics of the purple sweet potato gel candy produced are sweet and sour taste, candy aroma, solid chewy texture, light purple color. The panelists' acceptance of the making of purple sweet potato gel candy through the hedonic test results showed that the most favored by the Panelists were the product code 472 with a composition of 60 grams of sweet potato, 75 grams of gelatin, 75 grams of sugar, 1 gram of himalaya salt.